Strengthening the Cyber Terrorism Law Enforcement in Indonesia: Assimilation from Islamic Jurisdiction - Bakry, Muammar; Syatar, Abdul; Abubakar, Achmad; Risal, Chaerul; Ahmad, Ahmad; Amiruddin, Muhammad Majdy (International Journal of Criminology and Sociology, 2021)
The threat of terrorism is exacerbated by technology. It leads to a new term called Cyberterrorism. Apparently, this threat has not received appropriate space in the legal regulations in Indonesia. Therefore, this paper aims to strengthen legal action against cyberterrorism. This strengthening is obtained by assimilating Islamic law through the normative juridical method. The data are sourced from related news and updated journals. Researchers found that the assimilation of Islamic law products into positive law in Indonesia was in the form of Hirabah Punishment, Rebel Punishment, or Takzir. This idea is expected to be a consideration for policymakers in updating their laws so that they can reduce terrorism crimes, especially in cyberspace.